Effects of 7-weeks competitive training period on physiological and mental condition of top level judoists - Garatachea, N.; Hernández-Garcia, R.; Villaverde, C.; González-Gallego, J.; Torres-Luque, G. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: We examined hormonal and haematological parameters and the profile of mood states (POMS) in top level judoists undertaking a 7-week competitive training period in a real contest. METHODS: Participants were 10 top level judoists belonging to the Spanish National Team. Training load was calculated by multiplying the training session intensity by the duration of the training session. The judoists competed in two official events on weeks 3 and 6 of the study. RESULTS:Urinary catecholamines increased at the end of the competitive period. Serum cortisol increased during the weeks in which judoists competed, confirming the existence of and anticipatory cortisol response to exercise; although we failed to find serum testosterone increases. Because of leukocyte values did not change, except monocytes, we speculate that the intensity of training was not sufficiently high to evoke injury to muscle tissue. Anger, tension, and fatigue increased according with training load, suggesting that the training exercise led participants into a negative psychological state. CONCLUSION: Findings indicate that during competitive periods, judoists suffer hormonal and mood changes according to training load and competitive events. Results support the usefulness of monitoring biological and psychological markers during season in order to adjust training loads and periods of recovery.